Project elephant - Ring, Susan; Pittsburgh Zoo (Pittsburgh, Pa.) (Mankato, MN : Weigl Publishers, 2003)
Provides information about elephants through a look at a calf born at the Pittsburgh Zoo, examining its early life, its parents, and elephant characteristics and behaviors; and discusses how zoos can help prevent elephant extinction.
"Developed in collaboration with the Pittsburgh Zoo and PPG Aquarium"--T.p. verso.
Includes index.
School Library Journal.
Horn Book.
Science and Children (N.S.T.A.).
4.2
Keywords: African elephant -- Infancy -- Juvenile literature; Zoo animals -- Pennsylvania -- Pittsburgh -- Juvenile literature; African elephant; Elephants; Animals -- Infancy; Zoo animals; African elephants; Elephants; Animal babies; Zoo animals; Elephants; Zoo animals; African elephant; Animals -- Infancy; Animals -- Africa